International trade policies in the era of globalization - Ozer, Ahu Coskun, 1981- (Business Science Reference, an imprint of IGI Global, 2020)
"This book examines the effects of foreign trade policies on foreign trade. It also explores the impact of the implementation of tariff and non-tariff measures on countries"--